FORMULASI FLAKES BERBASIS PATI GARUT DENGAN FORTIFIKASI ZAT BESI (Fe) UNTUK PERBAIKAN STATUS BESI REMAJA PUTRI - Chairil, Muhammad Mifthah Faridh; Kustiyah, Lilik (Jurnal Gizi dan Pangan, 2014)
The aim of this study was to formulate flakes made from arrowroot starch, soy protein isolate, and tapioca starch, which was added by taburia (consisted of multivitamin and minerals), sugar, salt and water. Flakes made of 10% soy protein isolate substitution was the most acceptable organoleptically than 20 and 30% soy protein isolate. Taburia fortification was then applied to this formula, 50% RDA of iron fortification was more reasonable to be selected than 25% one according to contribution of iron. Addition of chocolate flavor resulted in improving acceptability of flakes. Flakes with chocolate flavor has better physical properties.Contribution of flakes with chocolate flavor to adolescents RDA of protein and iron were 5.14—6.02% and 39.46%; and flakes without chocolate flavor were 5.82—6.80% and 68.92%, respectively. Flakes with chocolate was better in acceptability, but lower in nutrients content than flakes without chocolate flavor.